Legal Reform in Space: Navigating the Future of Cosmic Mining Regulations - Putro, Yaries Mahardika; Tarigan, Muhammad Insan; Al Asyari, Haekal (Journal of Law and Legal Reform, 2025)
The rapid advancement of space technology and the increasing demand for natural resources have heightened interest in extraterrestrial resource extraction, particularly Helium-3 from the Moon. However, space mining is contentious in international law, as only a few nations currently have the capability to extract these resources. This raises concerns among emerging space actors, like Indonesia, about equitable benefit-sharing as outlined in the Outer Space Treaty (OST). The Moon Agreement aimed to create a legal framework for lunar resource utilization, but its effectiveness is limited due to the lack of ratification by major spacefaring nations. This situation has sparked international debate on whether current space law adequately governs space mining or if legal reform is needed to ensure fair access and sustainable development. The absence of a universally recognized regulatory regime, akin to the seabed mining framework under the United Nations Convention on the Law of the Sea (UNCLOS), complicates the issue further. This paper uses a normative juridical method to explore the legal challenges of space mining, especially from the perspective of emerging space actors. Without a comprehensive regulatory framework, unchecked exploitation of lunar resources could lead to severe environmental consequences and exacerbate disparities in access to space resources. Legal reforms are necessary to promote sustainability and equitable participation, limiting the dominance of spacefaring nations and protecting the rights of emerging space actors in the expanding space economy.